Plasma Indoleamine 2, 3-Dioxygenase Activity Is Associated With the Size of the Human Immunodeficiency Virus Reservoir in Patients Receiving Antiretroviral Therapy. (10th August 2018) - Chen, Jun; Xun, Jingna; Yang, Junyang; Ji, Yongjia; Liu, Li; Qi, Tangkai; Wang, Zhenyan; Zhang, Renfang; Shen, Yinzhong; Ponte, Rosalie; Mehraj, Vikram; Routy, Jean-Pierre; et al.
Abstract : Identification of factors associated with the size of the Human Immunodeficiency Virus reservoir remains a priority for HIV cure research. We report that the activity of Indoleamine 2, 3-Dioxygenase, an immunoregulatory enzyme that metabolizes tryptophan to kynurenines, is associated with the size of the HIV reservoir. Abstract: Background: Indoleamine 2, 3-dioxygenase (IDO) is an immunoregulatory enzyme that metabolizes tryptophan to immunosuppressive kynurenines. We investigated whether IDO activity is associated with the size of HIV reservoir. Methods: Total human immunodeficiency virus (HIV) DNA in peripheral blood mononuclear cells (PBMCs) from 127 HIV-infected patients receiving antiretroviral therapy (ART) was quantified. Tryptophan and kynurenine concentrations, as well as microbial translocation markers, were measured in plasma samples. T-cell activation and exhaustion in PBMCs were assessed by flow cytometry. Results: Elevated IDO activity prior to ART correlated with on-ART HIV DNA ( r = 0.35, P = .004), but was not associated with pre-ART HIV DNA. A median duration of 15 months of ART significantly decreased IDO activity; however, these levels were still higher than those observed in HIV-uninfected controls. Among treated participants, IDO activity positively correlated with their concurrent HIV DNA ( r = 0.36, P < .0001). Multivariate model showed an independent association of pre-ART CD4/CD8 ratio (adjusted odds ratio [aOR], 0.75 per 0.1 increase [95% confidence interval CI, .62–.91]) and on-ART IDO activity (aOR, 1.09 per nM/μM increase [95% CI, 1.04–1.14]) with higher levels of HIV DNA on-ART. A lack of association of the microbial translocation markers was observed with the size of HIV reservoir. HIV DNA positively correlated with the proportions of activated CD4 T and CD8 T cells and exhausted CD4 T cells. Conclusions: We observed a positive correlation between IDO activity and total HIV DNA in blood, highlighting the important role of immunometabolic aberrations in HIV persistence.